KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN METODE SURVEY, QUESTION, READ, RECITE, DAN REVIEW (SQ3R) - Fitriyani, Dwi (JURNAL PESONA, 2017)
This study aims to know studentsâ reading comprehension using SQ3R Method for the third semester students of Indonesia Language and literature education major of STKIP Muhammadiyah Pringsewu Lampung. The research sample was 40 students. In collecting the data, the researcher used triangulation tehcnique ( observation, interview, and documentation), and test technique. Validity test data used triangulation technique by checking the data in the same resource. In analysing the data, the researcher employed data triangulation (reducing the data, dicplaying the data, and verifying). The research procedure was implemented in four steps: plan, action, reflection,and evaluation. This study was done in two cycles. The result shows that SQ3R method can improve studentsâ reading comprehension. In the first cycle, 16 students or 40% students were notÂ  pass in reading comprehension. Then studentsâreading comprehension was improved 100% in the second cycle.